Perception About Business Education in the Tourism Domain and the Hospitality Industry - Nicolae Lupu; Mihail Ovidiu Tanase; Ana-Maria Nica (Amfiteatru Economic Journal, 2014)
The research aimed at the importance of a well-structured business education, with a view to preparing the future employees for the requirements of the labour market, has become the central point in many key-sectors of the economy. This paper is based on having identified a gap in scientific research in Romania, that of the need to link the skills offered by the higher education system to the needs of the employers from the tourism and hospitality industry. Therefore, the following question arouses: ,,What is the perception of both employers and future employees on the training system for the tourism and hospitality industry domain?”. With a view towards obtaining an answer, the authors have chosen a descriptive type of research, i.e. a survey among students enrolled in the professional masters program Business Administration in Tourism, as well as among managers of representative hotels in Bucharest. The results show that the perception of students and professionals, respectively, are distributed comparatively, - on many aspects, such as the vocational character of the profession, the importance of attitude, of the theoretical and practical grounding -, but also that the profile of the graduate of an economic faculty of tourism, in the posture of candidate on the labour market, is quite controversial. Developing the curriculum, accordingly to the needs of the employers, will reduce the gap between the academic environment, as a supplier of professional formation, and the labour market, as a place where the labour force demand and supply meet.
Keywords: A23; J23; J24; L83; O15; P46; 330; business education; professional skills; hospitality industry; tourism